Association of plasma lactoferrin levels with disease severity in glaucoma patients - Wang, Zuo; Liu, Donghua; Yuan, Hang; Li, An; Wang, Jinxia; Zhu, Xiong; Xiu, Wenbo; Zhang, Gao; Chen, Yang; Chen, Lingling; Xiao, Xiao; He, Chong; et al. (Frontiers in Medicine, 2024)
Objective To explore the relationship between plasma lactoferrin (Lf) and glaucoma, assessing the clinical utility of Lf in glaucoma. Methods A cross-sectional study involved 161 glaucoma patients and 115 healthy controls, with a follow-up of 14 subjects after approximately 2 years. Plasma Lf markers were quantified using ELISA, comparing levels between glaucoma patients and healthy controls, and analyzing plasma Lf across different glaucoma severity grades. Results Glaucoma patients had significantly elevated plasma Lf levels compared to healthy controls (p < 0.001). Higher plasma Lf levels correlated with more severe disease stages (HPA grades showed ρ = 0.435, p < 0.001; AGIS grades showed ρ = 0.436, p < 0.001) and reduced retinal nerve fiber layer (RNFL) thickness (RNFL thickness showed ρ = −0.204, p = 0.024). ROC curve analysis demonstrated the efficacy of glaucoma markers in differentiating early-stage from advanced glaucoma. Conclusion Plasma Lf levels are significantly associated with glaucoma severity and may be involved in the pathogenic progression of the disease.